Micronutrient status of cultivated mushrooms of India - Kumar, Sanjeev; Sagar, Prof Anand (Mushroom Research, 2023)
The present study evaluated the micronutrients, vitamins and minerals of five cultivated mushrooms of India viz., Agaricus bisporus (button mushroom), Calocybe indica (milky mushroom), Flammulina velutipes (winter mushroom), Pleurotus florida (oyster mushroom) and Volvariella volvacea (paddy straw mushroom). The vitamins detected in 100g dry weight of cultivated mushrooms were Vitamin A (2.44-3.94 mg), Vitamin B1 (0.003-0.018mg),Vitamin B2 (0.189-1.625), Vitamin B3 (42.62-98.16 mg), Vitamin B5 (0.059-0.405 mg), Vitamin B6 (15.1 mg in A. bisporus),Vitamin B9 (0.121-0.214 mg),Vitamin B12 (0.96-1.68 μg), Vitamin C (24.2-81.1mg), Vitamin D (0.339-0.747 mg), and Vitamin E (24.8 mg in A. bisporus, 38.1 mg in V. volacea and 56.6 mg in P. florida). The mineral contents found in 100g dry weight were K (3.7-6.2 g), Mg (0.11-0.24 g), P (0.58-1.42 g), Ca (31.3-88.3 mg), Na (27.38-101.4 mg), Mn (0.55-1.49 mg), Fe (6.45-29.4 mg), Se (0.036 mg in V. volvacea and 0.426 mg in A. bisporus), Mo (0.012-0.062 mg), Zn (2.39-8.725 mg), Cu (0.7-7.17 mg) and Cr (0.02-0.159 mg). It is evident from the results that the cultivated mushrooms are valuable source of vitamins and minerals and they can contribute significantly to our fight against malnutrition.